Oral hygiene behaviour automaticity: Are toothbrushing and interdental cleaning habitual behaviours?. (November 2020) - Raison, M.H.; Corcoran, R.; Burnside, G.; Harris, R.
Abstract: Objectives: Toothbrushing and interdental cleaning are critical to maintaining good oral health. Literature is beginning to suggest that these behaviours may be conducted automatically, although the instigation ('deciding to do') and execution ('doing') of these behaviours has never been examined separately. The objective of this study was to test a theoretically informed supposition that oral hygiene behaviours in adults are automatic behaviours. Methods: One hundred and fifty participants attending three types of dental providers covering emergency and routine dental services, completed a questionnaire. The self-reported behavioural automaticity index scale (SRBAI) was used to measure behavioural automaticity. Results: Morning toothbrushing SRBAI scores were higher than evening scores (Z=-3.315, p = 0.001). Automaticity scores for instigating both toothbrushing and interdental cleaning were also higher compared to execution (toothbrushing: Z=-2.601, p = 0.009 and interdental cleaning: Z=-2.256. p = 0.024). Toothbrushing automaticity scores were associated with age, gender and self-efficacy, whereas interdental cleaning automaticity scores were associated with intention. Individuals in lower socio-economic status (SES) occupations had significantly higher automaticity scores for interdental cleaning compared to those with higher SES roles. Conclusions: A high proportion of people undertake toothbrushing and interdental cleaning automatically, especially in relation to embarking on these behaviours. This is most pronounced in morning toothbrushing. Clinical significance: Promoting improvements in oral hygiene behaviour toothbrushing and interdental cleaning are key strategies in preventing caries and periodontal disease. A greater understanding of what prompts and sustains these behaviours helps inform how behaviour change efforts should be approached.